Efficacy of Rock Phosphate and Super Phosphate with Phosphate Solubilizer (Bacillus megatherium var. phosphaticum) on Cowpea in a Rainfed Entisol - Duraisami, V P; Mani, A K (Annals of Arid Zone, 2016)
Field experiments were conducted for two years during 1998 and 1999 in an Entisol (Typic Ustorthent) with two phosphatic fertilizers, viz., Single Super Phosphate (SSP) and Rock Phosphate (RP) at two levels each viz., 25 kg ha,l (100%) and 18.75 kg ha’i (75%). with and without seed soaking and phosphobacterium (/3acilllls lIlega/hail/1Il var. phosphaticum) on cowpea under rainfed condition. The results indicated that the yield. uptake and economics were improved by the sources of P. Application of 18.75 kg P20S ha’l as RP, coupled with phosphobacterium and seed soaklllg resulted in maximum yield (537 kg ha,l) with higher net return (Rs. 4544 ha’l) and H/C ratio (3.39). The recovery of applied P and the residual soil P were also improved by the P solubilizer and seed soaking. A positive P balance could be noticed under the P-treated plots, while it was negative in the untreated control.